Primary English Teachers’ Technology Integration Experiences: A Cross-Cultural Narrative Inquiry - Hertiki Hertiki; Hendra Tedjasuksmana; Y.G. Harto Pramono; Saran Chantalay (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2026)
The rapid advancement of technology has significantly reshaped educational practices, particularly in primary English classrooms. While previous research has largely focused on the technical and pedagogical dimensions of technology integration, limited attention has been given to teachers’ personal narratives across diverse cultural contexts. Addressing this gap, this study examines how four primary English teachers from Norway, Indonesia, Malaysia, and Scotland narrate their experiences of integrating technology, with emphasis on emotion, reflection, and professional identity. Adopting a narrative inquiry approach, data were collected through in-depth online interviews and were analyzed thematically to construct contextualized accounts of teachers’ transitions from traditional to digital practices. The findings reveal three key insights: (1) technology integration presents both opportunities and challenges; (2) teachers’ use of technology is shaped by personal motivation, professional identity, and infrastructural support; and (3) while technology enhances student engagement, confidence, and participation, it also introduces challenges related to time management, digital inequality, and developmental appropriateness. Although limited by a small sample size and context-specific design, the study offers important implications for teacher-centered professional development and policy initiatives aimed at ensuring equitable access to technological resources. It further underscores the importance of teacher agency and context-sensitive support in fostering inclusive, meaningful, and sustainable technology integration in primary education. Future research should involve larger samples, more diverse educational settings, and mixed-method approaches to extend and validate these findings.